A systematic review of psychosocial factors associated with emotional adjustment in in vitro fertilization patients - Rockliff, Helen E.; Lightman, Stafford; Rhidian, Emily; Buchanan, Heather; Gordon, Uma; Vedhara, Kavita (Oxford University Press, 2014)
BACKGROUND